2015
DOI: 10.1016/j.trb.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Transit technology investment and selection under urban population volatility: A real option perspective

Abstract: eS789 the experienced raters was found to be 0.48 with a novice rater ICC of 0.48 as well. The ICC between all the raters was 0.33. Conclusion(s):This constitutes poor reliability. The poor reliability of the technique testing the length of LD was identified and addressed in order for adequate usage thereof, in research and in practice. Recommendations of a new technique to test the length of LD were provided by the researcher.A suggestion was made regarding a manner of testing its reliability.Implications: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Burke and Demirag [27] found that the traffic demand risk emanates within the operational phase, while the toll revenue calculation is conducted before the time when PPP becomes operational (at the planning stage). Otherwise, recently researchers focused more on the highway investment size, investment timing, and corresponding solutions [28][29][30]; these studies can be helpful for the highway investment and avoid the invest risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Burke and Demirag [27] found that the traffic demand risk emanates within the operational phase, while the toll revenue calculation is conducted before the time when PPP becomes operational (at the planning stage). Otherwise, recently researchers focused more on the highway investment size, investment timing, and corresponding solutions [28][29][30]; these studies can be helpful for the highway investment and avoid the invest risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The critical population density is identified for selection of transit modes. Li et al (2015) approach a similar problem as in Chen et al (2015) in different ways. The uncertainty in population is explicitly considered by characterizing the population growth with a geometric Brownian motion.…”
Section: Selection Of Pure Transit Modesmentioning
confidence: 99%
“…Supplementary proof of (7) and (10) related to this article can be found in Appendix B. Supplementary proof of static analysis for the thresholds q * and M * related to this article can be found in Appendix C. (Supplementary Materials) …”
Section: Supplementary Materialsmentioning
confidence: 99%
“…There is a compelling need to account for time-dependent uncertainty within network designs and project investment due to their irreversible characteristics [25,26]. Li et al [10] proposed a RO model to address investment and selection in transit technology given a volatile city population by considering the spatial use equilibrium of a city. Chow et al [27] investigated the management of a transportation network in an uncertain market, applying the RO approach and dynamic programming to obtain the value of flexibility and to defer and redesign a network.…”
Section: Introductionmentioning
confidence: 99%